FEMINIST PERSPECTIVES IN SELECT PLAYS OF MANJULA PADMANABHAN AND MAHASWETA DEVI - V. Simila; P. Saravanakumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the feminist perspectives evident in select plays by Manjula Padmanabhan and Mahasweta Devi, two influential Indian writers known for challenging traditional gender norms and societal structures. Drawing from Simone de Beauvoir’s concepts of The Other, immanence and transcendence, Situation and Freedom, and myths and reality, the paper examines how these playwrights confront and deconstruct prevailing myths and stereotypes surrounding women in Indian society. Through an analysis of Padmanabhan’s Escape and The Island of Lost Girls, as well as Devi’s Mother of 1084 and other works, the paper highlights the portrayal of women’s struggles and agency within their respective contexts. Padmanabhan’s dystopian narratives challenge societal norms and expectations, while Devi’s realistic portrayals shed light on the intersectionality of gender, caste, and socio-economic factors in shaping women’s experiences.